Rapid point-of-care testing for COVID-19: quality of supportive information for lateral flow serology assays - Kierkegaard, Patrick (BMJ Open, 2021)
OBJECTIVE: There is a lack of evidence addressing several important human factors questions pertaining to the quality of supportive information provided by commercial manufacturers that can affect the adoption and use of lateral flow serology assays in practice. We aimed to: (1) identify and assess the quality of information that commercial manufacturers provided for their point-of-care tests (POCTs) and (2) examine the implications of these findings on real-world settings. DESIGN: We used a content analysis methodology in two stages to systematically, code and analyse textual data from documents of commercial manufacturers. A deductive approach was applied using a coding guide based on the validated Point-of-Care Key Evidence Tool (POCKET) multidimensional checklist. An inductive approach was used to identify new patterns or themes generated from our textual analysis. SETTING: Publicly available supportive information documents by commercial manufacturers for lateral flow serology, were identified and gathered from online searches. PARTICIPANTS: Supportive information documents retrieved from online searches over 3 months (March 2020 to June 2020). RESULTS: A total of 79 POCTs were identified that met the study inclusion criteria. Using the POCKET coding guide, we found that the quality of information varied significantly between the manufacturers and was often lacking in detail. Our inductive approach further examined these topics and found that several statements were vague and that significant variations in the level of details existed between manufacturers. CONCLUSIONS: This study revealed significant concerns surrounding the supportive information reported by manufacturers for lateral flow serology assays. Information transparency was poor and human factor issues were not properly addressed to mitigate the risk of improper device use, although it should be noted that the results of our study are limited by the data that manufactures were prepared to disclose. Overall, commercial manufacturers should improve the quality and value of information presented in their supporting documentation.